KARAKTERISTIK DAN NILAI SITUS WARISAN BUDAYA DUNIA CATUR ANGGA BATUKAU KABUPATEN TABANAN - Wahyuni, Anak Agung Nyoman Sri; Guna, I Nyoman Ariana; Sadguna, Dewa Nyoman (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
Catur Angga Batukau is one of The Cultural Landscape of Bali Province: The Subak System as a Manifestation of the Tri Hita Karana Philosophy, which has the widest coverage area that poses management challenges as well as local communities who do not know about the characteristics and important values of the world cultural heritage site Catur Angga Coughau. This problem is exacerbated by the lack of information that explains the characteristics and important values contained in the world cultural heritage site CaturAngga Coughau, making it very vulnerable to oblivion. Based on these problems, this research is very important to be carried out indescribing the characteristics and important values contained in the world cultural heritage site Catur Angga Coughau. The dataanalysis technique used is qualitative descriptive analysis, which will explain and describe the characteristics and important values contained in the cultural heritage of the Angga Coughau Chess world. The results of the data analysis explain that the culturalheritage of the Angga Coughau Chess world has characteristics based on the concept of mandala consisting of Pura Luhur Muncaksari, Pura Luhur Petali, Pura Luhur Besikalung, Pura Luhur Tambawaras and Pura Luhur Coughau and has important values in various fields, namely history, science, education, culture and religion.